Strategi Regulasi Diri Mahasiswa Di Tengah Arus Tekanan Digitalisasi Dan Etika Bermedia Sosial - Kurnia Ahmad Susilo; Ellen Prima (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The rapid wave of digitalization and the complexity of social media ethics in the modern era present new challenges for university students' learning dynamics, particularly regarding the risks of cognitive distraction and digital moral degradation. This study aims to analyze students' self-regulated learning strategies in maintaining academic focus and internalizing social media ethics amidst the pressures of the digital environment. Utilizing a qualitative approach with a case study method, data were gathered through in-depth interviews, digital observations, and documentation involving university students. The results indicate that students with high self-regulation capabilities are able to implement adaptive strategies, which include: metacognition in limiting screen time,  managing a digital learning environment with minimal distractions, and  self-control rooted in ethical awareness (digital citizenship) when interacting in virtual spaces. Conversely, weak self-regulation correlates with higher levels of academic procrastination and vulnerability to digital ethical conflicts. The implications of this study emphasize the critical importance of integrating digital literacy and character building based on self-regulation into the higher education curriculum to foster a resilient, productive, and ethical academic generation in cyberspace.